If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -1.26 = ln(4 + x) Reorder the terms: -1.26 + 2x = ln(4 + x) -1.26 + 2x = (4 * ln + x * ln) -1.26 + 2x = (4ln + lnx) Solving -1.26 + 2x = 4ln + lnx Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1lnx' to each side of the equation. -1.26 + -1lnx + 2x = 4ln + lnx + -1lnx Combine like terms: lnx + -1lnx = 0 -1.26 + -1lnx + 2x = 4ln + 0 -1.26 + -1lnx + 2x = 4ln Add '1.26' to each side of the equation. -1.26 + -1lnx + 1.26 + 2x = 1.26 + 4ln Reorder the terms: -1.26 + 1.26 + -1lnx + 2x = 1.26 + 4ln Combine like terms: -1.26 + 1.26 = 0.00 0.00 + -1lnx + 2x = 1.26 + 4ln -1lnx + 2x = 1.26 + 4ln Reorder the terms: -1.26 + -4ln + -1lnx + 2x = 1.26 + 4ln + -1.26 + -4ln Reorder the terms: -1.26 + -4ln + -1lnx + 2x = 1.26 + -1.26 + 4ln + -4ln Combine like terms: 1.26 + -1.26 = 0.00 -1.26 + -4ln + -1lnx + 2x = 0.00 + 4ln + -4ln -1.26 + -4ln + -1lnx + 2x = 4ln + -4ln Combine like terms: 4ln + -4ln = 0 -1.26 + -4ln + -1lnx + 2x = 0 The solution to this equation could not be determined.
| 4x+9x-7x=7+5 | | T(n-T)=-S | | 8(6x-7)=0 | | X+-7=8 | | 40(x-20)=10x+40 | | [2y-7]=13 | | 7r+5=5r+35 | | t2u2r/rut3 | | 16y/4-81 | | C=-22x+-x^2 | | 3v+9-11v=-23 | | 2^5/3 | | 3/4 | | -6+2s=-9+5 | | 3x=ln(4) | | w+2w+18w=0 | | 26=5x+3x+2 | | -3x+2=x-2 | | 5y-3xy-8=0 | | 100/95*x/875 | | -10s=7 | | 100/95*X/875=.05 | | 40x=48x | | (-2)=3 | | x+6y-52=-7 | | 23y/6-5y/2=8 | | x+(-9)=-2 | | [8x]=72 | | 5x-15+1=5x-14 | | 1.1/9 | | 93=3x+18 | | 4^4/3 |